Senna occidentalis (L.) Link and Senna hirsuta (L.) H. S. Irwin & Barneby: constituents of fruit essential oils and antimicrobial activity. Issue 11 (3rd June 2019) - Essien, Emmanuel E.; Thomas, Paul S.; Ascrizzi, Roberta; Setzer, William N.; Flamini, Guido
Abstract: Senna occidentalis and S. hirsuta are mostly gathered from the wild for medicinal use and have a disagreeable odour when crushed. The volatile oils isolated from fresh fruits of S. occidentalis and S. hirsuta were subjected to gas chromatography (GC), gas chromatography-mass spectrometry (GC-MS) and antimicrobial assays. GC and GC-MS analyses permitted the identification of 58 constituents. S. occidentalis oil was dominated by cyperene (10.8%), β-caryophyllene (10.4%), limonene (8.0%) and caryophyllene oxide (6.8%). The main components of S. hirsuta fruit oil were benzyl benzoate (24.7%), τ-cadinol (18.9%), 2, 5-dimethoxy- p -cymene (14.6%) and β-caryophyllene (5.1%). S. occidentalis fruit oil exhibited better antimicrobial activity (MIC 78–312 μg/mL) against Escherichia coli, Staphylococcus aureus, Bacillus subtilis and Aspergillus niger compared with S. hirsuta oil. The compositions and the activities of the fruit essential oils of S. occidentalis and S. hirsuta are reported for the first time. Abstract :